2000
DOI: 10.1007/s004240050950
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the mdr-1b gene in the kidney of rats subjected to dehydration or a high-salt diet

Abstract: The localization of the multidrug resistance gene (mdr-1b) messenger ribonucleic acid (mRNA) along the rat nephron and its regulation was investigated under two different experimental situations: dehydration and high-Na+ diet. The mdr-1b mRNA was detected in glomeruli, proximal tubule segments, cortical and medullary thick ascending limbs, inner medullary collecting ducts and thin limbs of Henle's loop. Using the ribonuclease (RNase) protection assay (RPA), the abundance of mdr-1b mRNA was shown to be 35% less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…One possible reason for such variability is that the ABCB1 gene is polymorphic, and two of its single-nucleotide polymorphisms (SNPs), rs1128503 and rs1045642, may modify the final protein conformation, compromising its membrane stability and substrate recognition 7,8. Finally, it has been reported that the ABCB1 expression may also be modulated by plasma aldosterone9 or cortisol,10 as well as by dietary salt and dehydration 9…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for such variability is that the ABCB1 gene is polymorphic, and two of its single-nucleotide polymorphisms (SNPs), rs1128503 and rs1045642, may modify the final protein conformation, compromising its membrane stability and substrate recognition 7,8. Finally, it has been reported that the ABCB1 expression may also be modulated by plasma aldosterone9 or cortisol,10 as well as by dietary salt and dehydration 9…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental conditions did not allow the distinction between the highly similar sequences of mdr1 and mdr3. Morales et al (2000) demonstrated that in renal tubular cells the mdr1 isoform activity can be modulated by aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…59 In addition to the fact that a high-salt diet alters the expression of ABCB1 in rats, we also showed that the mRNA expression of ABCB1 was diminished in adrenalectomized rats, suggesting that aldosterone could be an endogenous regulator of this protein. 56 More recently, it was shown that aldosterone activity in the plasma, brain, and heart was significantly higher in ABCB1-deficient mice. 60 The data obtained in the above studies, performed in different animal models, pointed to a possible role for ABCB1 in hypertension and were followed by additional studies in humans.…”
Section: Evidence For the Interplay Between Abcb1 And Hypertension: Rmentioning
confidence: 99%
“…56 In addition, in a recent study, we showed that ABCB1, but not ABCC1, is downregulated in peripheral blood mononuclear cells and in the kidneys of spontaneously hypertensive rats. 57 Our results were confirmed by a study of another group showing that a high-salt diet reduced the expression levels of the abcb1a and abcb1b genes in the rat liver and kidney but increased their expression levels in the duodenum, jejunum, and ileum, suggesting that the regulation of this protein is tissue specific.…”
Section: Evidence For the Interplay Between Abcb1 And Hypertension: Rmentioning
confidence: 99%